2021
DOI: 10.1590/1518-8345.4510.3426
|View full text |Cite
|
Sign up to set email alerts
|

Quality of the documentation of the Nursing process in clinical decision support systems

Abstract: Objective: to compare the quality of the Nursing process documentation in two versions of a clinical decision support system. Method: a quantitative and quasi-experimental study of the before-and-after type. The instrument used to measure the quality of the records was the Brazilian version of the Quality of Diagnoses, Interventions and Outcomes, which has four domains and a maximum score of 58 points. A total of 81 records were evaluated in version I (pre-intervention), as well as 58 records in version II (p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 19 publications
1
4
0
6
Order By: Relevance
“…Another finding of our study is linked to the variable Nursing Intervention, which showed a lower rate of overall non-completeness. This finding converges with the literature (25) regarding the fact that the records of this information have a higher frequency in the patient's record than other NP steps. However, nursing interventions showed an increasing temporal trend towards noncompleteness in the records of PHC nurses regarding TB.…”
Section: Unsatisfactory Completeness Of Nurses' Records In the Medical Records Of Users With Tuberculosissupporting
confidence: 91%
See 1 more Smart Citation
“…Another finding of our study is linked to the variable Nursing Intervention, which showed a lower rate of overall non-completeness. This finding converges with the literature (25) regarding the fact that the records of this information have a higher frequency in the patient's record than other NP steps. However, nursing interventions showed an increasing temporal trend towards noncompleteness in the records of PHC nurses regarding TB.…”
Section: Unsatisfactory Completeness Of Nurses' Records In the Medical Records Of Users With Tuberculosissupporting
confidence: 91%
“…In Brazil, NP documentation is a formal requirement, developed in all areas where users' nursing care occurs. This formality has the perspective of enhancing the quality of the nurse's care and nursing assistance (25) .…”
Section: Discussionmentioning
confidence: 99%
“…Segundo outro estudo, que também avaliou a qualidade da documentação do PE, as informações desse domínio são relevantes na construção do PE, pois é por meio delas que é possível a identificação de problemas reais ou potenciais. 17 Logo, ficam evidentes a relevância dos instrumentos para a coleta de dados, sua contribuição para com os registros de enfermagem, a importância da elaboração deles com pauta em evidências científicas para contemplar o máximo de informações relevantes e a contribuição com a qualidade da assistência prestada no período de internação. Os próximos itens analisados dizem respeito à dimensão das Intervenções de Enfermagem, embasadas no julgamento clínico a partir da análise dos dados das etapas anteriores, e constituem-se de ações e atividades visando ao bem-estar do paciente.…”
Section: Métodounclassified
“…Historicamente o PE surgiu nos Estados Unidos, na década de 1950, inicialmente como guia para os estudantes de enfermagem e posteriormente nos serviços de enfermagem para dar maior autonomia à profissão, favorecer o cuidado holístico e proporcionar a continuidade da assistência (Oliveira & Peres, 2021). No Brasil, teve seu início na década de 1970 através dos estudos precursores de Wanda de Aguiar Horta que se embasou na teoria da motivação humana de Maslow, autor que postulou que todo ser humano possui necessidades comuns e hierarquizadas.…”
Section: Introductionunclassified
“…Autores conceituados afirmam ainda que há dificuldade para estabelecer o diagnóstico de enfermagem, atribuindo como causas o desconhecimento dos sinais e sintomas, das necessidades básicas alteradas e da nomenclatura destas necessidades, entre outras (Lopes, 2000;Azevedo at al., 2019). Um estudo realizado em unidades de saúde administradas pelo Estado de São Paulo, demonstrou que de 416 setores estudados, apenas 288 registravam quatro das cinco etapas do PE, fato que ratifica o pensamento de que mesmo sendo reconhecido como uma ferramenta importante para a gerência do cuidado do paciente e para a própria afirmação da profissão enquanto ciência, há necessidade de se implementar diversas estratégias para que se amplie a implementação do PE no Brasil (Oliveira & Peres, 2021).…”
Section: Introductionunclassified